AKTIVITAS KOMUNIKASI KELEMBAGAAN PENGELOLA HOMESTAY DI DESA SAWARNA BAYAH KABUPATEN LEBAK BANTEN - Irmulansati Tomohardjo; Ida Anggraeni Ananda; Santa Margaretha Niken Restaty; Samsul Hadi (Jurnal Pariwisata Pesona, 2021)
Sawarna Village, Bayah District, Lebak Regency, Banten Province has a beach area that can be visited by tourists and is known as a tourist destination for Sawarna Beach. Then the creativity of local residents emerged in their daily activities by managing homestays for tourists who want to live and enjoy Sawarna Beach. The communication process through institutions around Sawarna Village, Bayah District, Lebak Regency, is one of the supports for homestay managers to carry out activities to add productive value. So the purpose of this study is to explain how the institutional communication activities for homestay managers in Sawarna Bayah Village, Lebak Regency, Banten Province. The research method is a case study, the type of research is descriptive qualitative, with in-depth interview data collection techniques. The results showed that interactive institutional communication activities for homestay managers were carried out through tourism awareness groups (Pokdarwis), PKK, the Tourism Office, village institutions, several institutions such as PTP, INHUTANI, PLN and the PKL community. They coordinate about supporting of government events, awareness of the economic value of the products produced and interventions for empowering homestay managers.